COVID-19 pandemic and food security: Strategic agricultural budget allocation in Indonesia - Akbar Akbar; Rahim Darma; Andi Irawan; Mahyuddin; Feryanto Feryanto; Rida Akzar (Journal of Agriculture and Food Research)
The COVID-19 pandemic has exposed significant vulnerabilities in Indonesia's food security, highlighting the need for more strategic agricultural budget allocation. This study addresses the issue of inadequate budgeting techniques that fail to effectively support food production and distribution during crises. The primary objective is to develop a tailored framework that optimises budget allocations to strengthen Indonesia's food security in the face of socio-economic and geographical challenges. Using a multi-dimensional research approach, the study involves key stakeholders from the Ministry of Agriculture, the Ministry of Finance, and the Ministry of National Development Planning, employing methods such as in-depth interviews, focus group discussions, and data collection from primary and secondary sources. The research utilises the Analytical Hierarchy Process (AHP) with the Expert Choice 2000 program to systematically evaluate decision-making options. Findings reveal the necessity of a resilient framework that balances short-term emergency responses with long-term strategies, focusing on increasing production capacity, improving seed quality, expanding land availability, and adopting advanced agricultural technologies. The study contributes to the policy landscape by offering a structured agricultural budgeting framework and policy recommendations aimed at mitigating disruptions, enhancing productivity, and supporting sustainable agricultural practices. It also emphasizes the importance of sensitivity analysis in budget planning to inform strategic decisions. The study recommended targeted investments in production capacity, a reevaluation of rice import regulations, and the adoption of innovative technologies to ensure a resilient and sustainable food system in Indonesia.